Electromechanical properties of carbon nanotubes - Juarez-Mosqueda, Rosalba; Ghorbani-Asl, Mahdi; Kuc, Agnieszka; Heine, Thomas (Journal of Physical Chemistry C, 2014)
Electromechanical properties of carbon nanotubes were studied using Born-Oppenheimer molecular dynamics simulations within the QM/ MM approach. The indentation of nanotubes was simulated using an AFM tip. The electronic structure and transport response to the mechanical deformations were investigated for different deflection points starting from perfect unperturbed systems up to the point where the first bonds break. We found the dependence of the force constant on the diameter size: the smaller the diameter, the larger the k. For the metallic-armchair tubes, with diameters from 8 to 13 A, the conductance decreases only slightly under radial deformation, and a tiny band gap opening of up to 50 meV was observed.
CRIS-Team Scopus Importer:2023-03-20